2021
DOI: 10.3389/fpsyt.2021.640463
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Expression Pattern of Non-coding RNAs in Patients With Schizophrenia: With a Special Focus on Peripheral Blood as a Source of Expression Analysis

Abstract: Schizophrenia is a destructive neuropsychiatric disease with a median prevalence of 4.0 per 1,000 during the whole life. Genome-wide association studies have shown the role of copy number variants (generally deletions) and certain alleles of common single nucleotide polymorphisms in the pathogenesis of schizophrenia. This disorder predominantly follows the polygenic inheritance model. Schizophrenia has also been linked with various alterations in the transcript and protein content of the brain tissue. Recent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 71 publications
1
13
0
Order By: Relevance
“…A thorough understanding of transcription factors-miRNA-target gene axis may provide important clues to the molecular pathogenesis of SZ [ 16 , 49 ]. Of note, alterations within co-expression networks may occur with or without respective changes in the levels of its constituents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A thorough understanding of transcription factors-miRNA-target gene axis may provide important clues to the molecular pathogenesis of SZ [ 16 , 49 ]. Of note, alterations within co-expression networks may occur with or without respective changes in the levels of its constituents.…”
Section: Discussionmentioning
confidence: 99%
“…As a diverse but specific set of mRNA expression silencers, miRNAs regulate the expression of numerous genes and are considered to be vital regulators in neurodevelopment [ 14 , 15 ]. A large number of studies have shown that miRNA expression is abnormal in the brain and the peripheral blood of patients with SZ [ 16 , 17 ]. Several miRNAs, such as miR-124, miR-132, miR-134, and miR-137, have been reported to be associated with SZ [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pier Paolo Pandolfi and colleagues recommended a novel regulatory mechanism, known as competing endogenous RNA (ceRNA), in 2011 21 . It was suggested that cross-talk between both coding and non-coding RNAs such as lncRNAs, circular RNAs (circRNAs), and pseudogenes via miRNA response elements (MREs), as miRNA complementary sequences, leads to the formation of a large-scale regulatory network in diverse parts of the transcriptome 22 . According to the ceRNA hypothesis, RNAs transcripts can regulate each other by competing for shared miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNA MEG3 from module 7 functions as a ceRNA in ischemia-induced neuronal cell apoptosis (Liu et al, 2016 ). MEG3 is upregulated, and PINT (from module M10) is downregulated in SCZ post-mortem brain samples (Ghafouri-Fard et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%